Local Democracy as an Instrument for Socio-Political Change: The Case of Turkey - Saifullah Khan (Journal of Political Studies, 2020)
The study focuses the rise of Erdoğan and his strategy towards restoring the traditional Islamic face of Turkish society without antagonizing its European neighbors and avoiding direct confrontation with the dominant Secular Nationalist Troika. The four consecutive landslide victories for Justice and Development Party (AKP) in national as well as in local government elections have legitimized Erdoğan’s initiatives. The study argues that it was only local democracy that first enabled Erdoğan to take initiatives like banning public nudity, restricting consumption of alcohol in public places and allowing women to wear head scarf according to Islamic criteria even in the Europeanized city like Istanbul and later on, raised Erdoğan to the rank of President of Turkey where he amended the national constitution and narrowed the role of military and state Judiciary in political and administrative affairs of Turkey. The study draws a conclusion that when the national political environment of a highly centralized state is dominated by specific political elites in such a way that new forces don’t have any space to emerge and challenge the status quo than the political institutions at local levels can be used, beyond their normative assignments, for influencing the socio-political behavior of society in desired way.